2019
DOI: 10.1177/2041669519861982
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Music Tempo on Long-Distance Driving: Which Tempo Is the Most Effective at Reducing Fatigue?

Abstract: This study investigated how music tempo impacted drivers’ fatigue and quality of attention in a long-distance monotonous highway environment. Sixteen drivers were enrolled in four sessions of real-road driving tests under the following four music conditions: no music, slow tempo, medium tempo and fast tempo. Specifically, the drivers’ electroencephalogram parameters and eye movement parameters were recorded to measure their extent of fatigue and quality of attention, respectively. Of the three tempos, medium-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…Deeper understanding of the factors that influence driver behavior would help to design systems that increase safety by predicting human faults. Music is definitely an important factor concerning the behavior of a driver [17]; however, its impact is rarely subject to investigation. The reason for this is that the influence of music is quite complicated and highly individual.…”
Section: Motivationmentioning
confidence: 99%
“…Deeper understanding of the factors that influence driver behavior would help to design systems that increase safety by predicting human faults. Music is definitely an important factor concerning the behavior of a driver [17]; however, its impact is rarely subject to investigation. The reason for this is that the influence of music is quite complicated and highly individual.…”
Section: Motivationmentioning
confidence: 99%
“…It was also found to enhance the mind-wandering activities associated with DMN ( Taruffi et al, 2017 ). During long-range real-road driving tests, slow-tempo music can temporarily boost a driver’s quality of attention; after an extended period of driving, it significantly deteriorates the driver’s levels of energy and attention ( Li et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Li et al analyzed the influence of music rhythm on driver fatigue and attention quality in a long-distance monotonous highway environment. The study showed that middle-speed music was the best choice to relieve fatigue and maintain long-distance driving attention [19].…”
Section: Introductionmentioning
confidence: 99%